Perancangan User Interface Aplikasi Pembuatan Invoice Penjualan dengan Metode Prototyping Model pada CV Cokelat Turqy (Ziyadatur Rizqy) - M. Wahyu Hutomo Aji; Mahardeka Tri Ananta; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Micro, Small and Medium Enterprises (UMKM) play a very important role in terms of Indonesia's economic development. However, along with the rapid advancement of technology nowadays, there are still many UMKM players who have not yet utilized these technological advances. To develop the ability to record sales transactions, CV Cokelat Turqy (Ziyadatur Rizqy) has an urgency to need a good sales invoice generation application user interface design. Therefore, in this thesis project, a sales invoicing application user interface design is built that can help fulfill this urgency. The user interface prototype was designed using the Prototyping Model also using the System Usability Scale (SUS) as a parameter to measure the level of user satisfaction and the online test tool to measure the responsiveness of the prototype. Before testing, the task scenario is determined first as a guide for respondents in conducting the test. The results of testing the satisfaction level factor show that the resulting prototype has fallen into the category of good products. The results of testing the responsiveness level factor of the prototype on three different tablet device screen resolutions show that the resulting prototype is included in the responsive prototype.